False-positive HIV diagnoses: lessons from Ugandan and Russian research cohorts. Issue 1 (2nd January 2018) - Coleman, Sharon M.; Gnatienko, Natalia; Lloyd-Travaglini, Christine A.; Winter, Michael R.; Bridden, Carly; Blokhina, Elena; Lioznov, Dmitry; Adong, Julian; Samet, Jeffrey H.; Liegler, Teri; Hahn, Judith A.
Abstract : Background: Research studies rely on accurate assessment of entry criteria in order to maintain study integrity and participant safety, however, challenges can exist with HIV studies in international settings. Objective: Examine the unexpectedly high proportion of study participants with an undetectable HIV viral load found in Ugandan and Russian research cohorts meeting antiretroviral therapy (ART)-naïve entry criteria. Methods: Russian participants with documented HIV and ART-naïve status were recruited between 2012 and 2015 from clinical and non-clinical sites in St. Petersburg. Participants in Uganda were recruited from Mbarara Regional Referral Hospital from 2011 to 2014 with documented HIV infection via rapid diagnostic testing and recorded ART-naïve in the clinic database. HIV viral load testing of baseline samples was performed; the lower limit of detection was 500 copies/mL in Russia and 40 in Uganda. Due to an unexpectedly high proportion of participants with undetectable viremia, additional tests were performed: enzyme-linked immunosorbent assay HIV testing and testing for ART. Results: In Russia, 16% (58/360) had undetectable viremia; 3% (9/360) re-tested HIV-seronegative and 4% (13/360) tested positive for ART. In Uganda 11% (55/482) had undetectable viremia; 5% (26/482) re-tested HIV-seronegative, while <1% (4/482) tested positive for ART. Conclusions: In both Russia & Uganda, undetectable viremia was much higher than would be expected for an HIV-infected ART-naïve cohort. Misclassification of study participants was due to misdiagnosis of HIV with rapid diagnostic testing and inaccurate accounting of ART use. Confirmatory HIV testing could improve accuracy of participants meeting entry criteria for HIV infection as might increased scrutiny of medication use in an ART-naïve cohort.